2021
DOI: 10.1101/2021.10.02.462891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-dependent cell stiffening by tardigrade tolerance proteins through reversible formation of cytoskeleton-like filamentous network and gel-transition

Abstract: Tardigrades are able to tolerate almost complete dehydration by entering a reversible ametabolic state called anhydrobiosis and resume their animation upon rehydration. Dehydrated tardigrades are exceptionally stable and withstand various physical extremes. Although trehalose and late embryogenesis abundant (LEA) proteins have been extensively studied as potent protectants against dehydration in other anhydrobiotic organisms, tardigrades produce high amounts of tardigrade-unique protective cytoplasmic-abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…Here the 1D4 tag serves as a control to ensure that mVenus is not introducing artifacts. Additionally, sorbitol was selected to allow for comparisons to previous work carried out with CAHS proteins in cells 43 , 49 . CAHS proteins are known to form hydrogels in a concentration-dependent fashion in vitro and are suspected to do the same within cells during osmotic shock due to the observation of fiber-like formation and stiffening in vivo 25 , 34 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Here the 1D4 tag serves as a control to ensure that mVenus is not introducing artifacts. Additionally, sorbitol was selected to allow for comparisons to previous work carried out with CAHS proteins in cells 43 , 49 . CAHS proteins are known to form hydrogels in a concentration-dependent fashion in vitro and are suspected to do the same within cells during osmotic shock due to the observation of fiber-like formation and stiffening in vivo 25 , 34 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed sex-biased expression of several anhydrobiosis genes, hypothesized to play protective roles during anhydrobiosis (29-32, 90). For instance, CAHS genes are tardigrade-specific proteins that form gel filaments that possibly protect cells (91-93). Recent studies have observed tissue/organelle specificity for these proteins, which further implies the existence of orthologs with sex-specific expression (79).…”
Section: Discussionmentioning
confidence: 99%
“…Although these two protein families do not show sequence similarity with canonical LEA proteins, they both form alpha-helical structures under water-deficit conditions or upon TFE treatment, as reported for LEA proteins. Moreover, since 2021, multiple studies have reported the formation of higher-order structures by CAHS proteins [ 92 , 93 , 94 , 95 , 96 ]. These studies argue that purified recombinant CAHS proteins form fiber-like aggregates or gel-like lumps at high concentrations, as is assumed to occur with the onset of desiccation.…”
Section: Candidate Protective Molecules In Anhydrobiosis From Trehalo...mentioning
confidence: 99%